2013
DOI: 10.1016/j.bbrc.2013.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mutants disrupted in bacillithiol metabolism in Staphylococcus aureus

Abstract: Bacillithiol (BSH), an α-anomeric glycoside of L-cysteinyl-D-glucosaminyl-L-malate, is a major low molecular weight thiol found in low GC Gram-positive bacteria, such as Staphylococcus aureus. Like other low molecular weight thiols, BSH is likely involved in protection against a number of stresses. We examined S. aureus transposon mutants disrupted in each of the three genes associated with BSH biosynthesis. These mutants are sensitive to alkylating stress, oxidative stress, and metal stress indicating that BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 25 publications
1
56
4
Order By: Relevance
“…This discrepancy can be explained by the use of a nonstandard protocol for MIC assays in the prior study (e.g., the use of TSB instead of Mueller-Hinton broth, as suggested in the CLSI protocol [27]). In addition, the previous BSH studies have utilized transposon mutants (18,38) constructed in a strain cured of its plasmids (52); in addition, these studies did not complement the mutation to exclude any insertional polar effects that may have been caused by the transposon's insertion. We have confirmed here the contribution of both BSH and FosB to fosfomycin resistance in S. aureus using cis and trans complementation of our mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy can be explained by the use of a nonstandard protocol for MIC assays in the prior study (e.g., the use of TSB instead of Mueller-Hinton broth, as suggested in the CLSI protocol [27]). In addition, the previous BSH studies have utilized transposon mutants (18,38) constructed in a strain cured of its plasmids (52); in addition, these studies did not complement the mutation to exclude any insertional polar effects that may have been caused by the transposon's insertion. We have confirmed here the contribution of both BSH and FosB to fosfomycin resistance in S. aureus using cis and trans complementation of our mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, FosB was shown to mediate fosfomycin resistance in S. aureus through the use of BSH to disrupt the epoxide ring of fosfomycin (18,19,38). We investigated here the role of BSH in fosfomycin resistance mediated by FosB in a wide variety of methicillin-sensitive and methicillin-resistant S. aureus strains, including clinical isolates.…”
Section: Fosb Utilizes Bsh As a Substrate To Confer Fosfomycin Resistmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was postulated that detoxification of rifamycin S, a bacterial RNA polymerase inhibitor, might be bacillithiol transferase dependent in S. aureus [21, 26]. We found that BSH reacted directly with rifamycin S, primarily forming the reduced conjugate, BS-rifamycin SV, in a BstA-independent manner at pH 7.0 and pH 6.0 with a rate of >35 μM min −1 (Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 72%
“…Thiol analysis of the bshB Tn-mutant has shown that unlike B. subtilis bshB1 and bshB2 single mutants, the S. aureus bshB mutant does not produce BSH, indicating that there is no compensating BshB activity (data not shown and [26]). Indeed, the wild type S. aureus USA300 (JE2) dialyzed cell-free extract showed robust BCA activity (670 ± 70 nmoles min −1 mg −1 ) similar to that of the bstA mutant extract (570 ± 10 nmoles min −1 mg −1 ), whereas the bshB mutant extract showed BCA activity at just 10% of the wild type level (70 ± 13 nmoles min −1 mg −1 , Figure 6B).…”
Section: Resultsmentioning
confidence: 99%